Feasibility of endoscopic mucosal resection as salvage treatment for patients with local failure after definitive chemoradiotherapy for stage Ib, Ii, and Iii esophageal squamous cell cancer. Issue 1 (1st January 2014) - Makazu, M.; Kato, K.; Takisawa, H.; Yoshinaga, S.; Oda, I.; Saito, Y.; Mayahara, H.; Ito, Y.; Itami, J.; Hamaguchi, T.; Yamada, Y.; Shimada, Y.
Summary: Local failure after definitive chemoradiotherapy (CRT) for stage IB, II, and III esophageal cancer is one of the causes of poor outcome. Endoscopic mucosal resection (EMR) is an effective treatment for superficial esophageal cancer. However, its feasibility as a salvage treatment for local recurrent or residual tumors after definitive CRT for stage IB, II, and III esophageal cancer remains unclear. Between January 2000 and February 2008, 274 patients with stage IB, II, and III esophageal squamous cell cancer excluding T4 received definitive CRT at the National Cancer Center Hospital, Japan. Of these patients, nine patients with local recurrence after achieving complete response and two patients with residual tumor underwent salvage EMR. The technique of salvage EMR involved a strip biopsy method. We retrospectively reviewed the 11 patients (13 lesions). Characteristics of all 11 patients were as follows: median age of 69 (range: 45–78); male/female: 10/1; baseline clinical stage (Union for International Cancer Control 7th) IB/IIA/IIB/III: 1/3/7/0. The depth of resected tumor was limited to the mucosal layer in seven lesions and submucosal in six lesions. En bloc resection was performed on six lesions (46%). The vertical margin was free of cancer cells in 11 lesions (84.6%). No major complications, such as hemorrhage requiring blood transfusion and perforation, were experienced. At a median follow-up period of 38.9 months (range: 5.3–94 months) after salvage EMR, no recurrence was detected in six patients (54%). Local recurrence was detected in five patients (27%). Of these patients, two had lung metastasis simultaneously, and one was also detected lung metastasis 2 months after the detection of local recurrence. The 5-year survival rate after salvage EMR was 41.6%. Salvage EMR is a feasible treatment option for local recurrent or residual lesions after definitive chemotherapy and/or radiotherapy for stage IB, II, and III esophageal squamous cell cancer.